Using a 2D detector array for meaningful and efficient linear accelerator beam property validations. (8th November 2014) - Ritter, Timothy A.; Gallagher, Ian; Roberson, Peter L.
Abstract : Following linear accelerator commissioning, the qualified medical physicist is responsible for monitoring the machine's ongoing performance, detecting and investigating any changes in beam properties, and assessing the impact of unscheduled repairs. In support of these responsibilities, the authors developed a method of using a 2D ionization chamber array to efficiently test and validate important linear accelerator photon beam properties. A team of three physicists identified critical properties of the accelerator and developed constancy tests that were sensitive to each of the properties. The result was a 14‐field test plan. The test plan includes large and small fields at varying depths, a reduced SSD field at shallow depth for sensitivity to extra focal photon and electron components, and analysis of flatness, symmetry, dose, dose profiles, and dose ratios. Constancy tests were repeated five times over a period of six weeks and used to set upper and lower investigation levels at ± 3 SDs. Deliberate variations in output, penumbra, and energy were tested to determine the suitability of the proposed method. Measurements were also performed on a similar, but distinct, machine to assess test sensitivity. The results demonstrated upper and lower investigation levels significantly smaller than the comparable TG‐142 annual recommendations, with the exception of the surrogate used for output calibration, which still fell within the TG‐142 monthly recommendation. Subtle changes in output, beam energy, and penumbra were swiftly identified for further investigation. The test set identified the distinct nature of the second accelerator. The beam properties of two photon energies can be validated in approximately 1.5 hrs using this method. The test suite can be used to evaluate the impact of minor repairs, detect changes in machine performance over time, and supplement other machine quality assurance testing. PACS numbers: 87.56bd, 87.56Fc